(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Introduction: Metastasis from breast carcinoma accounts for the majority of the death from this disease. Hybrid imaging like PET-CT is an integral part of staging breast carcinoma, selection of therapy, and detection of metastases. Patients and methods: Histopathologically proven breast carcinoma patients before or after surgery, chemotherapy and radiotherapy who had undergone whole body 18F-FDG PET-CT at Institute of Nuclear Medicine & Allied Sciences, (INMAS) Suhrawardy, between May, 2024 to December, 2024 were retrospectively studied to assess the pattern of metastases. Results: A total of 33 breast carcinoma patients with a mean age of 51.4 ± 12 years were studied. Among them infiltrating ductal cell carcinoma (IDC) was found in 22 (66.7%), lobular carcinoma in 5 (15.1%), mucinous carcinoma in 2 (6.1%), triple negative breast carcinoma in 2 (6.1%), ductal cell carcinoma in situ in 1(3.03%) and metaplastic carcinoma in 1(3.03%). Out of 22 IDC cases, 15 (68%) were diagnosed with lung metastasis and 3 (60%) out of 5 cases of lobular breast carcinoma metastasized to bones. Other than axillary lymph nodes, breast carcinoma often metastasizes to mediastinal lymph nodes. Two patients presented with rare metastasis in the ovary and adrenal gland. Conclusions: 18F-FDG PET-CT findings of breast carcinoma have a substantial impact on therapeutic strategies, and stage migration may require a significant change in the management protocol to provide proper treatment. Bangladesh J. Nuclear Med. 28(1): 31-38, 2025